The Effect Of Work Discipline On Employee Performance At The Dairi Regency Regional Disaster Management Agency Office - Roy Enddharta Tumangor; Mesra B (Yayasan Multidimensi Kreatif, 2024)
This study aimed to analyze the effect of Work Discipline on Employee Performance at the Regional Disaster Management Agency (BPBD) in Dairi Regency. The population in this study consisted of 43 employees. The hypothesis test results showed that Work Discipline had a positive and significant effect on Employee Performance, with a t-value of 43.223, which was greater than the t-table value of 2.01954, and a significance value of 0.000, which is less than 0.05. The regression coefficient showed that for every 1-unit increase in Work Discipline, Employee Performance would increase by 0.987 units, assuming other variables remained constant. Additionally, the determination test results showed an Adjusted R Square value of 0.960 or 96.00%, indicating that Work Discipline had a very high impact on Employee Performance, while the remaining 6.00% was influenced by other factors not examined in this study. Therefore, Work Discipline had a positive and significant effect on Employee Performance at the Regional Disaster Management Agency (BPBD) in Dairi Regency